El cruel abrazo del dolor: la endometriosis y sus representaciones - Galli, Ida (2024)
Endometriosis is a chronic disease of the female genital tract, the etiology of which is still unclear. The purpose of this paper is to analyze, from a biopsychosocial perspective, the structure of social representations of endometriosis of women with this disease and healthy women. To this end, an exploratory survey was conducted by administering an online questionnaire. The results made it possible to identify those particular type of social representations, the controversies, articulated differently and often contradictory in their peripheral elements. These results provide a useful basis for the construction of intervention strategies to avoid the “epistemological purgatory” in which many women are forced to live due to the discrepancy between the subjective experience of endometriosis and its expert knowledge.